Efektivitas Penyuluhan Media Audio Visual Terhadap Tingkat Pengetahuan Ibu Tentang Imunisasi Dasar di PMB Suratni - Syilvia Syilvia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Backround: Basic immunization is a crucial step in preventing communicable diseases that can be controlled through vaccination in infants. However, the coverage of basic immunization in Indonesia has not yet reached the desired target. One of the factors influencing immunization coverage is the low level of maternal knowledge about immunization. This issue was identified in a preliminary study conducted at PMB Suratni. The objective of this study is to evaluate the effectiveness of health education using audio-visual media in improving mothers' knowledge about basic immunization at PMB Suratni.Methods: This study employed a quasi-experimental design with a control group. A total of 50 mothers with infants aged 0–12 months at PMB Suratni were selected as respondents. The intervention group received health education using audio-visual media, while the control group was given conventional lecture-based education. Data were collected through pretest and posttest questionnaires and analyzed using the Wilcoxon test and N-Gain score.Results: Expert evaluations of the material and media categorized them as appropriate. The study results from both interventions indicated a significant improvement in maternal knowledge in the group that received audio-visual education compared to the control group. The average N-Gain score in the intervention group was 0.72 (high category), whereas the control group scored 0.45 (moderate category). The Wilcoxon test showed a p-value of <0.05, indicating a significant difference between the two groups.Conclusion: Health education using audio-visual media is proven to be more effective in enhancing mothers' knowledge about basic immunization compared to the lecture method. Audio-visual health education can serve as an interactive and informative alternative in health education programs to improve basic immunization coverage in infants.